2015
DOI: 10.32601/ejal.460588
|View full text |Cite
|
Sign up to set email alerts
|

The role of translation in vocabulary acquisition: A replication study

Abstract: This study aimed to test the findings of earlier research indicating that EFL students could better learn new vocabulary via translation from L1 rather than by encountering it in the context of L2 sentences. Over one thousand Thai freshmen students were allocated to one of three groups to learn 30 unfamiliar English words. One group studied translation pairs, a second studied the words in the context of English sentences with graphic illustrations and the third had English sentences, illustrations and Thai tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
7
2
Order By: Relevance
“…However, the current study significantly differs from Alroe and Reinders (2015) who showed through their research that studying vocabulary contextually is better than studying it through translation. Similar to Alroe and Reinders (2015); Marqués-Aguado and Solís-Becerra (2013) presented different results to this study when they found evidence that translation has little contribution to L2 vocabulary development and that the learners' vocabulary knowledge could be improved through other strategies than translation.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the current study significantly differs from Alroe and Reinders (2015) who showed through their research that studying vocabulary contextually is better than studying it through translation. Similar to Alroe and Reinders (2015); Marqués-Aguado and Solís-Becerra (2013) presented different results to this study when they found evidence that translation has little contribution to L2 vocabulary development and that the learners' vocabulary knowledge could be improved through other strategies than translation.…”
Section: Discussioncontrasting
confidence: 85%
“…Nonetheless, in the communicative approach, there is a common assumption that using translation makes no contribution to the foreign language development (Marqués-Aguado & Solís-Becerra, 2013). Alroe and Reinders (2015) also explored the results of previous studies through a replication study, finding that EFL learners could learn new vocabulary faster by translating them rather than learning them in context. The results of this study showed that the group who learned the words through translation did not do better than the two other groups who contextually learned them (Alroe & Reinders, 2015).…”
Section: The Effect Of L1 Translation On Vocabulary Knowledgementioning
confidence: 99%
“…However, the current study significantly differs from Alroe & Reinders' (2015) who showed through their research that studying vocabulary contextually is better than studying it through translation. Similar to Alroe & Reinders, Barzegar and Rahimy (2012) presented different results to this study when they found evidence that the learners' vocabulary knowledge could be better developed through reading tasks than translation.…”
Section: The Impact Of the Strategy Of Translating On Vocabulary Knowcontrasting
confidence: 85%
“…He found that less proficient students who studied via translation did indeed do significantly better than those who studied contextually when they were tested by translation, though not when tested contextually. However, the study was problematic in that it had no delayed post-test and a later replication of the experiment found no advantage for learning vocabulary via translation (Alroe and Reinders 2015). Moreover, in his conclusion Prince himself expressed reservations about the use of translation: 'It may indeed be plausibly suggested that a highly developed ability to learn words via translation links may in some cases be detrimental to the establishment of the skills and strategies required to handle discourse ' (1996:486).…”
Section: Literature Reviewmentioning
confidence: 99%